2017
DOI: 10.1080/20008198.2017.1302691
|View full text |Cite
|
Sign up to set email alerts
|

Posttraumatic growth and depreciation six years after the 2004 tsunami

Abstract: Background: Posttraumatic growth (PTG) has been reported after various types of potentially traumatic events, as a part of the personal recovery process among survivors. Even negative changes in survivors’ life view, known as posttraumatic depreciation (PTD), have been identified as an additional aspect in the personal recovery processes. Objective: To examine how the type of exposure experienced by survivors of a natural disaster, the 2004 Southeast Asia tsunami, influenced self-reported PTG and PTD six years… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 39 publications
3
17
0
Order By: Relevance
“…First, the variables traumatic event and growth were not correlated. An explanation could lie in the fact that we did not ask the participants to rate the subjective severity, as it is an individual's perception that allows the event to be comprehended as traumatic (Michélsen, Therup-Svedenlöf, Backheden, & Schulman, 2017). Second, our findings indicated that the trauma group experienced significantly less growth in the dimension of 'relation with others' compared to the non-trauma group.…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“…First, the variables traumatic event and growth were not correlated. An explanation could lie in the fact that we did not ask the participants to rate the subjective severity, as it is an individual's perception that allows the event to be comprehended as traumatic (Michélsen, Therup-Svedenlöf, Backheden, & Schulman, 2017). Second, our findings indicated that the trauma group experienced significantly less growth in the dimension of 'relation with others' compared to the non-trauma group.…”
Section: Discussionmentioning
confidence: 76%
“…It would have been preferable to include an additional open-ended question regarding possible negative changes because a minority of participants went with their answer about possible positive changes beyond the asked question and reported about negative changes as well. Thus, one could assume that also the other participants would have reported about negative changes (posttraumatic depreciation) if gotten the chance as, for example, in the study of Michélsen et al (2017). By extension, the PTGI-42 (Cann, Calhoun, Tedeschi, & Solomon, 2010), which assesses positive (posttraumatic growth) and negative (posttraumatic depreciation) changes, could be used.…”
Section: Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Arnberg, Hultman, Michel, & Lundin, 2013) and the 2004 Southeast Asia tsunami (e.g. Michélsen, Therup-Svedenlöf, Backheden, & Schulman, 2017), both leading to hundreds of Swedish casualties, as well as the recent deployment of Swedish peacekeeping forces around the world, have highlighted the psychosocial consequences of trauma. More recently, the refugee crisis has set off many activities related to culturally informed trauma services.…”
Section: Psychotraumatology In Swedenmentioning
confidence: 99%
“…2.In two articles (Michélsen et al, 2017; Mueller-Pfeiffer et al, 2010), Bayes was used but without any argumentation.…”
Section: Notesmentioning
confidence: 99%